Proceedings 1999 IEEE International Conference on Computer Design: VLSI in Computers and Processors (Cat. No.99CB37040)
DOI: 10.1109/iccd.1999.808592
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing the performance potential of dynamic cache line sizes

Abstract: In this paper we examine the application of offline algorithms for determining the optimal sequence of loads and superloads (a load of multiple consecutive cache lines) for direct-mapped caches. We evaluate potential gains in terms of miss rate and bandwidth and find that in many cases optimal superloading can noticeably reduce the miss rate without appreciably increasing bandwidth. Then we examine how this performance potential might be realized. We examine the effectiveness of a dynamic online algorithm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Vleet et al [24] proposed using off-line profiling to determine the fetch size upon a cache miss. However, the lack of dynamism render these static approaches less effective when faced with a data set that changes rapidly during program execution.…”
Section: Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Vleet et al [24] proposed using off-line profiling to determine the fetch size upon a cache miss. However, the lack of dynamism render these static approaches less effective when faced with a data set that changes rapidly during program execution.…”
Section: Prior Workmentioning
confidence: 99%
“…Recent research [13,17,18,23,24] indicates that there are large spatial variations in cache line usage both within and across programs. In the presence of such drastic variations, a fixed cache line size results in a sub-optimal design point.…”
Section: Introductionmentioning
confidence: 99%
“…This expectation may be based on profile information [9,25], hardware detection of strided accesses [17] or spatial locality [ 12,14,25], or compiler annotation of load instructions [23]. Optimal off-line algorithms for fetching a set of noncontiguous words [24] or a variable-sized aligned block [25] on each miss provide bounds on these techniques. Pollution may also be reduced by prefetching into separate buffers [13,23].…”
Section: Related Workmentioning
confidence: 99%
“…Przybylski [ 181 analyzed cancelling an ongoing demand fetch (after the critical word had returned) on a subsequent miss, but found that performance was reduced, probably because the original block was not written into the cache. Our scheduling technique is independent of the scheme used to generate prefetch addresses; determining the combined benefit of scheduling and more conservative prefetching techniques [9,12,14,17,25] is an area of future research. Our results also show that in a large secondary cache, controlling the replacement priority of prefetched data appears sufficient to limit the displacement of useful referenced data.…”
Section: Related Workmentioning
confidence: 99%
“…Vleet and co-authors [28] propose offline profiling to select fetch size upon a miss. Guided region prefetching [29] uses compiler hints to direct both spatial and non-spatial (e.g., pointer-chasing) prefetches.…”
Section: Related Workmentioning
confidence: 99%